Early Netherlandish paintings : rediscovery, reception and research - Buren, Anne van; Buren, Anne van; Ridderbos, Bernhard; Ridderbos, Bernhard; Veen, Henk Th. van; Veen, Henk Th. van (Amsterdam University Press, 2005)
Objects and Questions (Bernhard Ridderbos) -- Collecting Early Netherlandish Paintings in Europe and the United States (Till-Holger Borchert) -- From Waagen to Friedländer (Bernhard Ridderbos) -- Realism, Renaissance and Nationalism (Wessel Krul) -- Technical Examination (Jeltje Dijkstra) -- The Corpus of Fifteenth-Century Painting in the Southern Netherlands and the Principality of Liège (Henri Pauwels) -- Patronage (Maximiliaan P.J. Martens) -- Iconography and Iconology (Craig Harbison)